Prinsip Manajemen Pembiayaan Lembaga Non Bank Syariah (Studi Kasus KSPPS BMT Khoiru Ummah Jawa Timur) - Mila Arlina, Agustin; Yazid, Muhammad; Agus Hidayat, Ahmad (Jurnal Ilmiah Ekonomi Islam, 2023)
Islamic financial institutions are divided into two main categories: Islamic banking institutions and non-banking Islamic financial institutions. One common form of Islamic financial institution found in society is the Shariah-based Savings and Loans Cooperative, which is a microfinance institution. Shariah-based financing involves the provision of funds or receivables based on a contract or agreement between the Savings and Loans Cooperative and another party, obligating the financed party to repay the funds or receivables after a specified agreed-upon period. Regarding financing, the Shariah-based Savings and Loans Cooperative requires financial analysis to ensure that cooperative members are capable of repaying the received financing. When applying for financing at the BMT Khoiru Ummah Savings and Loans Cooperative in East Java, applicants must go through several stages in accordance with the procedures established by the BMT Khoiru Ummah Savings and Loans Cooperative. Firstly, the applicant is required to become a member by opening an account at the BMT Khoiru Ummah Savings and Loans Cooperative. Then, they follow the financing procedure, which includes submitting a financing application, undergoing administrative selection and fulfilling document requirements, undergoing a survey process, evaluation by the committee, purchasing the desired goods, entering into a contractual agreement, delivering the goods or funds, and finally making installment payments and full repayment by the members.